Implementation of the STEAM Learning Method on Critical Thinking Skills in Early Childhood - Tasya Fitriana, Bela; Yusuf Sobri, Ahmad; Arafik, Muh. (Green Publisher Indonesia, 2024)
The objective of this study is to analyze and describe the application of the STEAM learning method in fostering critical thinking skills in early childhood education. This type of research is qualitative research with the aim of analyzing the implementation of the STEAM learning method on thinking abilities in early childhood. This research is needed so that educators can implement the STEAM learning method for the thinking abilities of young children. The subjects in this research were 10 students of Kindergarten B RA Bina Insani Al-Ma'ruf in Nglaban hamlet, Maron village, Banyakan district. This research uses observation data collection, in-depth interviews, and documentation. This research resulted that the implementation of STEAM learning at RA Bina Insani Al-Ma'ruf was carried out in every children's play activity. This learning involves several aspects of child development that are integrated and fun for children. In STEAM learning activities, the teacher acts as a facilitator and motivator according to the plans that have been prepared. This learning involves several aspects of child development that are integrated and fun for children. In STEAM learning activities, the teacher acts as a facilitator and motivator according to the plans that have been prepared. Basically, the implementation of STEAM learning at RA Bina Insani Al-Ma'ruf has principles based on attitudes, skills and knowledge.